What an amazing experience! The role of authenticity and engagement in upscale hotels - Rosado-Pinto, F.; Loureiro, S. M. C. (International Journal of Hospitality Management, 2023)
Authenticity and engagement are critical in hospitality experiences to offer a competitive advantage in upscale hotels. Yet, how these concepts are related is still scarcely analyzed. This study aims to i) understand the relationships between brand experience, brand authenticity, and customer engagement, (ii) analyze authentic pride and behavioral intentions as outcomes of brand authenticity and customer engagement. A quantitative study was conducted through a sample of 207 participants who had stayed in an upscale hotel in the previous 12 months. PLS-SEM was used to treat data. The data of the two focus groups were analyzed using NVivo. The findings demonstrate that a positive experience with the hotel brand influences the guests´ perception of authenticity and their engagement. The more authentic the hotel is perceived, the more engaged the customers tend to be. Findings also reveal that authentic pride and behavioral intentions are outcomes of brand authenticity and customer engagement.